The end of energy obesity : breaking today's energy addiction for a prosperous and secure tomorrow - Tertzakian, Peter; Hollihan, Keith (Hoboken, N.J. : John Wiley & Sons, 2009)
Nearly everything that defines our way of life requires energy-consuming devices, from cars, planes, trains, and air conditioning to lights and computers. And our global appetite for energy keeps growing as population and wealth obliges consumption on an unfathomable scale. Energy economist Peter Tertzakian explores how the world can reduce its energy appetite and change its diet of fuels for a prosperous and secure tomorrow, focuses on the most practical options that provide the highest leverage for resolving our energy problems, and reveals how evolving habits, lifestyles, mindsets and innovations--that might seem improbable now--will help curb our insatiable energy appetite.--From publisher description.
Pt. 1: The making of our energy appetite. After the banquet ; Whetting the energy appetite ; The first principle of energy consumption ; The world's factory -- Pt. 2: Elusive solutions. Breaking our energy diet ; Price and value ; Eating our efficiencies ; Complex carbons ; The maddening allure of the first principle -- Pt. 3: Thinking out of the box. The asymmetry principle ; Beyond nostalgia ; Conservation 2.0 ; Dissolving distance ; A low-carb, highly-scaleable diet ; The energy health craze -- Epilogue: Leadership on the commons.
0
Includes bibliographical references (p. 279-287) and index.
Keywords: Energy industries; Energy consumption; Economic development; Power resources